Neuroprotective Effect of Catalpol via Anti-Oxidative, Anti-Inflammatory, and Anti-Apoptotic Mechanisms - Yang, Chunjing; Shi, Zhengyuan; You, Longtai; Du, Yuanyuan; Ni, Jian; Yan, Dan (Frontiers in Pharmacology, 2020)
Neuroinflammation and neuro-oxidative damage are now considered to be key factors in the neurological diseases. Therefore, it is important to study anti-inflammatory and neuroprotective agents. The present study investigated the anti-inflammatory and neuroprotective effects of catalpol (CAT), and the potential molecular mechanisms involved. The findings revealed that CAT markedly downregulated pro-inflammatory mediator nitric oxide (NO) and cytokines, including interleukin (IL)-6 and tumor necrosis factor (TNF)-a in lipopolysaccharide (LPS)-treated BV2 microglial cells. Moreover, CAT significantly decreased the levels of intracellular reactive oxygen species (ROS) and malondialdehyde (MDA), increased superoxide dismutase (SOD) activity and glutathione (GSH) level, reversed apoptosis, and restored mitochondrial membrane potential (MMP) in primary cortical neurons stimulated with hydrogen peroxide (H2O2). Furthermore, mechanistic studies showed that CAT inhibited nuclear factor-κB (NF-κB) pathway and p53-mediated Bcl-2/ Bax/ casaspe-3 apoptotic pathway. Moreover, it targeted the Kelch-like ECH-associated protein 1(Keap1)/ Nuclear factor E2-related factor 2 (Nrf2) pathway. In summary, CAT may exert neuroprotective potential by attenuating microglial-mediated neuroinflammatory response through inhibition of the NF-κB signaling pathway. It blocked cortical neuronal oxidative damage by inhibiting p53-mediated Bcl-2/Bax/casaspe-3 apoptosis pathway and regulating Keap1/Nrf2 pathway. These results collectively indicate the potential of CAT as a highly effective therapeutic agent for neuroinflammatory and neuro-oxidative disorders.